Spies of the Balkans [large type] : a novel - Furst, Alan (Thorndike/Windsor/Paragon, 2010)
As war approaches northern Greece, the spies begin to circle--from the Turkish legation to the German secret service. In the ancient port of Salonika, Costa Zannis, a senior police official, head of an office that handles special "political" cases, risks everything to secure an escape route for those hunted by the Gestapo.